Excellent microwave absorption properties by tuned electromagnetic parameters in polyaniline-coated Ba0.9La0.1Fe11.9Ni0.1O19/reduced graphene oxide nanocomposites. Issue 58 (21st July 2017) - Luo, Juhua; Zuo, Yue; Shen, Pan; Yan, Zhu; Zhang, Kang
Abstract : The obvious enhancement of microwave absorption performance of Ba0.9 La0.1 Fe11.9 Ni0.1 O19 /reduced graphene oxide/polyaniline ternary nanocomposites in 2–18 GHz was observed. The minimum reflection loss can reach −49.1 dB with thickness of 1.9 mm. Abstract : Ba0.9 La0.1 Fe11.9 Ni0.1 O19 nanoparticles were prepared by a co-precipitation method, and Ba0.9 La0.1 Fe11.9 Ni0.1 O19 /reduced graphene oxide/polyaniline ternary nanocomposites (BF/RGO/PANI) were prepared by in situ polymerization. Microwave reflection loss, and the permittivity and permeability of BF/RGO/PANI nanocomposites were investigated in the frequency range 2–18 GHz. The prepared samples possessed excellent electromagnetic wave-absorbing performances, and the optimal impedance matching of BF/RGO/PANI nanocomposites was found. The minimum reflection loss reached −49.1 dB near the frequency of 14.08 GHz with a thickness of 1.9 mm and its absorption bandwidth with a reflection loss below −10 dB ranged from 12.4–16.72 GHz with a bandwidth of 4.32 GHz. Our study illustrates that the as-prepared BF/RGO/PANI nanocomposites are promising candidates for use in electromagnetic wave-absorbing materials.